Influence of pressurised cryogenic nitrogen technology on Arthrospira platensis (spirulina) preservation during storage. (24th November 2020) - Maujean, Elvis; Desobry, Stéphane; Gillet, Guillaume; Poupard, Nicolas; Desjardins‐Lavisse, Isabelle; Desobry‐Banon, Sylvie
Summary: In this study, preservation of spirulina using the new pressurised cryogenic nitrogen technology (PCN) was compared to classical methods used in laboratories and industry. Spirulina morphology was better preserved by PCN compared to unpressurised cryogeny and classical freezing at −20 °C that led to cells fragmentation. A 25% loss of Phycocyanin‐C content against 60% were measured after 98 days storage for 6‐Bar PCN process and frozen samples, respectively. The Total AntiOxidant Power (PAOT Liquid Technology ® ) was used for determination of total antioxidant and oxidant power of spirulina extracts. PAOT value of PCN samples was 50% higher than the frozen sample. From ABTS measurements on PCN spirulina fractions sonicated or not, it was suggested that pressurisation at 6 bars allowed a better preservation of free antioxidants (outside the cells) due to replacement of oxygen by nitrogen in the frozen beads. After dehydration, phycocyanin‐C content variation during storage at 20 °C and 33% RH showed higher loss for freeze‐dried spirulina treated at 0 compared to 6 Bars. Abstract : Equipment and efficiency of cryogenic treatment of spirulina vs classical freezing